Assessment of the Unemployment Situation of Vulnerable Groups in the Labour Market of the Baltic States - Okunevičiūtė-Neverauskienė, Laima; Pocius, Arūnas; Krutulienė, Sandra (Socialinė teorija, empirija, politika ir praktika, 2021)
The study analyses the unemployment situation of socially vulnerable groups in the Baltic States in the context of the European Union. The analysis of the unemployment rate is based on gender, age and duration of unemployment. Statistical analysis identified the most vulnerable groups in the labour market and those most sensitive to economics fluctuations. The study also evaluated the relationship of economic growth with employment of these groups. The research highlighted that in the Baltic countries, the global financial crisis more significantly affected vulnerable groups, mainly because of the impact of the crisis in 2009–2010. Hence these results differ from the general trend in unemployment rate of the target groups in the countries of the European Union. Unemployment rate at the EU level did not coincide with similar trends observed in the target groups in the Baltic States. In the Baltic States, the unemployment rate of the target groups started to grow earlier and faster than in the EU countries and it started to decrease much earlier than the EU unemployment rate indicators. In addition, in the Baltic countries, the growth of target group unemployment was significantly higher than the EU average. The fast and volatile growth of unemployment within the mentioned target groups shows that they had difficulties adapting to dramatically worsening conditions in the labour market in the Baltic States. The current pandemic situation in comparison to the global financial crisis of 2009–2010 has a less negative effect. The study revealed that unemployment rates in the Baltic States were close to the EU average. The research results also showed that men and the youth are sensitive to economic fluctuations in the Baltic States. On the one hand, unemployed men and the youth tend to more easily enter the labour market during economic upturns. On the other hand, in an economic downturn, these jobseekers face significant integration difficulties into the labour market and become more socially vulnerable. It is important to note that long-term unemployed people belong to the most vulnerable groups. People with low skills or qualifications face multiple barriers to labour market integration. Long-term unemployment leads to a loss of income, an erosion of skills, a higher incidence of health problems and increased household poverty.